Pre-Islamic Poetry As A Hermeneutic Tool In Qur'anic Exegesis: The Questions Of Nafi Ibn Al-Azraq As A Model/ الشعر الجاهلي كأداة هرمينوطيقية في التفسير القرآني: مسائل نافع بن الأزرق أنموذجا - Mustafa Kadad; Mehmet Çetinkaya; Nesim Aytepe; Mehmet Ata Deniz (Ijaz Arabi Journal of Arabic Learning, 2026)
This research addressing a central problematic in exegetical studies and philology: How did the literary heritage of a polytheistic milieu evolve into an indispensable hermeneutical tool for decoding the sacred monotheistic text? The study engages with this dialectical relationship, grounding its argument in the hypothesis that while Islam enacted a decisive doctrinal rupture with the Jahiliyyah, it did not institute a linguistic one; rather, it assimilated the prevailing linguistic system and semantically re-engineered it to serve the imperatives of Tawhid (monotheism). Employing a descriptive-analytical methodology, the paper examines applied models from Gharib al-Qur'an (obscure Quranic vocabulary), with a specific focus on the "Questions of Nafi' ibn al-Azraq" as a foundational historical document that legitimized the citation of poetic evidence (Istishhad) in exegesis. The study argues that the reliance of Abdullah ibn Abbas—the preeminent exegete—on poetry authored by polytheists or People of the Book (such as Umayya ibn Abi al-Salt) to elucidate Quranic lexicon constitutes an implicit acknowledgment that Arabic is a cumulative civilizational vessel. It posits that Quranic terminology did not emerge ex nihilo, but represents an extension of Semitic roots deeply embedded in the history of religions within the Arabian Peninsula. Furthermore, the research analyzes the phenomenon of "semantic shift" (resemantization), demonstrating how the Quran utilized identical pre-Islamic terms—such as Salah, Zakah, and Taqwa—yet divested them of their archaic content to recharge them with novel doctrinal payloads. This process renders the recourse to pre-Islamic poetry a hermeneutic necessity, not merely to ascertain legal definitions, but to trace the historical evolution of terminology and to appreciate the Quranic genius in transposing language from the sensory, material connotations prevalent in poetry to abstract, spiritual significations. The study concludes that pre-Islamic poetry functions not merely as the "Diwan of the Arabs" preserving tribal glories, but as the essential "Lexical Archive" of the Revelation. Consequently, the contemporary exegete requires the integrative tools of comparative philology and literary criticism, alongside traditional narration, to fully grasp the multi-dimensional nature of Quranic eloquence.